1998
DOI: 10.1161/01.atv.18.6.915
|View full text |Cite
|
Sign up to set email alerts
|

Role of Polymorphonuclear Leukocytes in Collar-Induced Intimal Thickening in the Rabbit Carotid Artery

Abstract: Abstract-In this study, the involvement of polymorphonuclear leukocytes (PMNs) in the development of intimal thickening was investigated. A fibromuscular intima was induced by placing a silicone collar around the rabbit carotid artery for 3 days or 2 weeks; the contralateral artery was sham operated. Rabbits received placebo treatments (groups 1 and 3), granulocyte-colony stimulating factor (group 2; G-CSF, 20, delivered by subcutaneous osmotic pumps), or an anti-CD18 monoclonal antibody (group 4; 1.5 mg/kg IV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 37 publications
(67 reference statements)
1
10
0
2
Order By: Relevance
“…25 In a cuff model with electrical stimulusinduced injury, mononuclear cell but not polymorphonuclear influx was shown to influence intimal thickening. 10 Although the present study was not designed to determine specific cell infiltrates, on the basis of previous results outlined above, 10,24 it is reasonable to speculate that polymorphonuclear influx does not significantly affect intimal thickening in the cuffinjury model. In the present report, the reduction of neointimal formation with antibody treatment was associated with reduced inflammatory infiltrates, suggesting further that monocyte/macrophage accumulation plays a role in promoting neointimal formation in injured arteries of apoE KO mice.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…25 In a cuff model with electrical stimulusinduced injury, mononuclear cell but not polymorphonuclear influx was shown to influence intimal thickening. 10 Although the present study was not designed to determine specific cell infiltrates, on the basis of previous results outlined above, 10,24 it is reasonable to speculate that polymorphonuclear influx does not significantly affect intimal thickening in the cuffinjury model. In the present report, the reduction of neointimal formation with antibody treatment was associated with reduced inflammatory infiltrates, suggesting further that monocyte/macrophage accumulation plays a role in promoting neointimal formation in injured arteries of apoE KO mice.…”
Section: Discussionmentioning
confidence: 82%
“…A rabbit cuff-injury model using antibody blockade of leukocytes showed that polymorphonuclear influx had little effect on SMC migration and intimal thickening. 24 It is notable that mononuclear cells were present in significant quantity only after prolonged exposure of the artery to LDL in vivo. This exposure to LDL also significantly increased intimal thickening.…”
Section: Discussionmentioning
confidence: 99%
“…As a second model of inflammation, we applied a non-occlusive cuff to the femoral artery, known to cause acute and then sustained vascular inflammation characterized by arterial infiltration of predominantly PMN (29,42,43). Indeed, within 24 h large numbers of inflammatory cells infiltrated the left femoral artery around which a cuff was placed, and leukocytes remained present in the "cuffed" artery for up to 14 days (Fig.…”
Section: Assessment Of 2-cl-e ϩ As a Surrogate Marker For Mpo/hocl Acmentioning
confidence: 99%
“…In contrast, Golino et al 23 reported that administration of a mAb against CD18 (R15.7) in a rabbit carotid model of injury involving placement of a constrictor around the vessel produced significant inhibition of neointimal hyperplasia. Van Put et al 24 also studied the effect of a mAb against CD18 (R15.7) in a collar-induced injury model in rabbit iliac arteries. They found plentiful neutrophils and small numbers of monocytes (CD14 positive cells) after injury.…”
Section: Role Of Leukocytes In Atherosclerosis and Experimentally Indmentioning
confidence: 99%